K-State Turfgrass Research 2002 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2002)
There is no rest for weary turfgrass managers in Kansas. In 2001, many of us were brought to our knees, literally -- it allowed for a better view of winter-damaged zoysiagrass, brown patch- infested tall fescue, or anthracnose-stricken creeping bentgrass. K-State's turfgrass research team is growing. We have four faculty in horticulture and one in plant pathology who dedicate their research efforts to improving turfgrass in Kansas. We also have balance, with work addressing fundamental turfgrass management problems like water management, stand establishment, weed control, and disease management. We are also striving to provide balance in serving needs across the industry including golf course superintendents, lawn care operators, and athletic field managers. Kansas turf industry members should be proud of the support they've provided for the K-State research program. You have helped make the program strong, and we'll only get stronger. This publication contains results of projects done throughout 2001 by K-State turfgrass researchers. Keep this research report handy -- it can be useful all year long. We also make this information available on our web site at: www.oznet.ksu.edu/horticulture. You can see many of these projects in progress on August 1, 2002 at the Kansas Turfgrass Field Day at the Rocky Ford Research Center in Manhattan.
Keywords: Kansas Agricultural Experiment Station contribution; no. 02-414-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 894; Weed control; Diseases; Bentgrass; Fescue; Ryegrass; Bluegrass; Bermudagrass; Buffalograss; Turfgrass